Graduate research : a guide for students in the sciences - Smith, Robert V., 1942-; Densmore, Llewellyn D.; Lener, Edward F. (London, UK : Academic Press is an imprint of Elsevier, 2016)
'Graduate Research' is an all-in-one resource for prospective and matriculated graduate students in the sciences. The newly revised edition includes updates to every chapter. It covers a range of topics including writing and preparation of research proposals, developing and refining teaching skills, and ethics and compliance areas such as research involving human subjects and animals.
Getting started -- Attitudes, commitments, and creativity -- Making choices -- Time management -- Principles of scientific research -- Ethics and the scientist -- Library and literature work -- Writing and speaking skills -- Preparing theses and disserations -- Presentation and publication of papers -- Research involving human subjects and animals and biohazards and laboratory safety -- Getting grant support -- The graduate researcher and teaching -- Getting a job -- Shaping a career.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed March 3, 2016).
Keywords: Research -- Methodology; REFERENCE -- Questions & Answers; Research -- Methodology; Electronic books